Bright and dark 1– soliton solutions to perturbed Schrodinger – hirota equation with power law nonlinearity via semi – inverse variation method and ansatz method - Subhaschandra Singh, S. (International Journal of Physical Research, 2017)
This paper studies perturbed Schrodinger Hirota equation with power law nonlinearity by obtaining its 1 – soliton solutions via He’s semi – inverse variation method and the Ansatz method and the results reveal that these methods are very effective ones for obtaining exact solutions to various types of nonlinear evolution equations appearing in the studies of science and engineering.